Safety assessment of the process Starlinger recoSTAR HDPE FC 1 – PET2PET used to recycle post‐consumer HDPE closures into food contact closures - Lambré, Claude; Barat Baviera, José Manuel; Bolognesi, Claudia; Chesson, Andrew; Cocconcelli, Pier Sandro; Crebelli, Riccardo; Gott, David Michael; Grob, Konrad; Mengelers, Marcel; Mortensen, Alicja; Rivière, Gilles; Steffensen, Inger‐Lise; et al. (EFSA journal, 2022)
The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Starlinger recoSTAR HDPE FC 1 – PET2PET. The process is intended to recycle food grade high‐density polyethylene (HDPE) closures from post‐consumer PET beverage bottle streams to produce recycled HDPE pellets using the technology Starlinger recoSTAR HDPE (FC 1). The recycled pellets are intended to be used at up to 100% for the manufacture of new closures for direct contact with mineral water and other beverages for long‐term storage at room temperature. The recycling process comprises the sorting of the HDPE closures from the bottles, their conventional recycling, their pre‐drying, their extrusion into pellets and their decontamination in a continuous reactor. The dossier contained insufficient data. Notably, the data provided did not include an adequate description of the process to allow a clear understanding of the main steps and operating parameters of the technology; the data did not allow to demonstrate that the challenge test is representative of the industrial process, hence, that it is suitable for determining the decontamination efficiency of the process; the data did not allow to estimate the residual concentration (Cres) for HDPE closures from PET beverage bottles. The Panel noted the limited efficiency of the technology to remove contaminants with a molecular weight above 400 Da and which would migrate into water and other beverages. Based on the submitted information, the Panel concluded that the applicant has not demonstrated in an adequately performed challenge test or by other appropriate evidence that the recycling process is able to reduce contamination of the HDPE flakes originating from PET beverage bottles to a concentration that does not pose a risk to human health.